Critical Role of Light in the Growth and Activity of the Marine N2-Fixing UCYN-A Symbiosis - Landa, Marine; Turk-Kubo, Kendra A.; Cornejo-Castillo, Francisco M.; Henke, Britt A.; Zehr, Jonathan P. (Frontiers in Microbiology, 2021)
The unicellular N2-fixing cyanobacteria UCYN-A live in symbiosis with haptophytes in the Braarudosphaera bigelowii lineage. Maintaining N2-fixing symbioses between two unicellular partners requires tight coordination of multiple biological processes including cell growth and division and, in the case of the UCYN-A symbiosis, N2 fixation of the symbiont and photosynthesis of the host. In this system, it is thought that the host photosynthesis supports the high energetic cost of N2 fixation, and both processes occur during the light period. However, information on this coordination is very limited and difficult to obtain because the UCYN-A symbiosis has yet to be available in culture. Natural populations containing the UCYN-A2 symbiosis were manipulated to explore the effects of alterations of regular light and dark periods and inhibition of host photosynthesis on N2 fixation (single cell N2 fixation rates), nifH gene transcription, and UCYN-A2 cell division (fluorescent in situ hybridization and nifH gene abundances). The results showed that the light period is critical for maintenance of regular patterns of gene expression, N2 fixation and symbiont replication and cell division. This study suggests a crucial role for the host as a producer of fixed carbon, rather than light itself, in the regulation and implementation of these cellular processes in UCYN-A.